Deterioration of building material at old shop building - Sharon Yong, Win Tin (2010)
Concrete is the main construction material in the Malaysia. In the past 40 years almost all buildings had a concrete skeleton with in-fill brick walls while timber has been widely used in many historic buildings in Malaysia. It can deteriorate easily if it is exposed to water penetration, high moisture content and loading beyond its capacity.Most building in Malaysia is not well maintained. The objective of this study is to identify material defect area in old shop building, to identify causes of material defect in old shop building, and to define major of material defect at the old shop building. To complete the objective, data will be collected by doing a research and survey at old shop building at research location (selected state only). The data will identify the type of defect which happened to the concrete and timber element of the building. Analysis carried out must be complete and accompanied by a graph so that readers are more interested in reading the report produced. Repair and maintenance would be the only action required to enable old shop buildings to survive.